ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN - Badjuri, Achmad; Nurul Ma’rifah, 12.05.52.0070 (Students' Journal of Accounting and Banking, 2016)
The study examines the effect of profitability, laverage, collateralizable assets, size, growth, current ratio, and investment opportunity on dividend policy. This research was conducted at the Indonesian Stock Exchange by using using a go public manufacturing company as the unit of analysis. The sampling method use purposive sampling with the observasion period from 2011 to 2013. Relationship and (or) influence betmeen variable is described by using multiple regression analysis. The result showed that profitability, laverage, collateralizable assets, current ratio, and investment opportunity have positive effect and significant to dividend policy. Whereas growth and size have positif and no significant effect on dividend policy.  Keywords: Dividend Policy, Profitability, Laverage, Collateralizable Assets, Size, Growth, Current Ratio and Investment Opportunity